PROFIL POLA ASUH ORANG TUA DALAM MENANAMKAN KEDISIPLINAN PADA ANAK USIA DINI ( Studi Kajian di Jorong VIII Tingkarang Kecamatan Rao Kabupaten Pasaman) - Mulyani, Refriza Widya (Bimbingan dan Konseling, 2014)
Background of this research is the parenting parents have impact on the growth and development of young children such discipline. This research aimed to describe: 1) Parenting of authoritarian parents in instilling discipline in early childhood. 2) Parenting of laissez faire parents in instilling discipline in early childhood. This research was conducted with descriptive qualitative approach which was undertaken in Jorong VIII Tingkarang Kecamatan Rao Kabupaten Pasaman. The main informants were 4 parents while the additional informants were 4 older siblings. The instrument used was the interview guide. Techniques used in analyzing data were data reduction, data presentation, and conclusion. The result of this research showed that: 1) Profiles parenting of authoritarian parents in instilling discipline to early childhood were parents forced the children and gave punishment to the child if the child did not obey parentsâ instruction and regulations. 2) Profiles parenting of laissez faire parents in instilling discipline to early childhood were parents had weak control to the child, parents gave freedom to the child what the child wants without guidancing and advicing the children.